Introduction: The Power of the Powerless at Forty. Issue 2 (May 2018) - Krapfl, James; Falk, Barbara J.
The guest editors of this special issue on The Power of the Powerless, forty years after its composition, here introduce the collection. They present the rationale for revisiting Václav Havel's classic essay and explain how this collection was inspired by an "international symposium by correspondence" that Jiří Suk of the Institute for Contemporary History and Kristina Andělová of Charles University, both in Prague, initiated in 2015, resulting in a collective volume entitled Jednoho dne se v našem zelináři cosi vzbouří: Eseje o Moci bezmocných . The guest editors briefly summarize each of the seventeen essays featured in the present collection and contextualize the newly annotated English translation of The Power of the Powerless that concludes it.